Social-Emotional Prevention Programs for Preschool Children's Behavior Problems A Multi-level Efficacy Assessment of Classroom, Risk Group, and Individual Level - Ştefan, Catrinel Alice (Springer International Publishing, 2018)
This book is aimed at exploring the relevance of social-emotional competencies for preventing preschool children's behavior problems. The content provides an overview of how evidence from fundamental research on social-emotional competencies can be translated in applied research for developing prevention programs. The Social-Emotional Prevention program framework is presented as a multi-focused (child, teacher, parent), hybrid approach for both high risk and non-risk preschoolers. The book offers a systematic and in depth evaluation of SEP efficacy including classroom, risk group, and individual level effects. Hence, the proposed approach employs different research designs and statistical methods to explore how behavioral changes occur as a result of children's participation to the intervention. Each study's findings are discussed in terms of corresponding implications for practice in schools, but also from a broader perspective including implications for policy makers in the field of early education. .